2019
DOI: 10.1093/ejcts/ezz240
|View full text |Cite
|
Sign up to set email alerts
|

The age-adjusted Charlson comorbidity index in minimally invasive mitral valve surgery

Abstract: OBJECTIVES Mitral valve repair is the preferred method used to address mitral valve regurgitation, whereas transcatheter mitral valve repair is recommended for high-risk patients. We evaluated the risk-predictive value of the age-adjusted Charlson comorbidity index (aa-CCI) in the setting of minimally invasive mitral valve surgery. METHODS The perioperative course and 1-year follow-up of 537 patients who underwent isolated or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In 330 spinal cord injured patients, Rochon et al [82] compared a count of ICD diagnostic codes and the CCI, and found that both predicted 18-month mortality, yet the Charlson Index outperformed the ICD diagnostic codes. In mitral valve patients undergoing minimally invasive surgery, the CCI and the Society for Thoracic surgeons score were highly correlated; both predicted 1-year mortality [83].…”
Section: Concurrent Validitymentioning
confidence: 99%
“…In 330 spinal cord injured patients, Rochon et al [82] compared a count of ICD diagnostic codes and the CCI, and found that both predicted 18-month mortality, yet the Charlson Index outperformed the ICD diagnostic codes. In mitral valve patients undergoing minimally invasive surgery, the CCI and the Society for Thoracic surgeons score were highly correlated; both predicted 1-year mortality [83].…”
Section: Concurrent Validitymentioning
confidence: 99%
“…In the process of decision making for surgical indication, it is important to consider patient comorbidities in addition to preoperative LVEF values of 30%–60% as this can also affect the outcomes of MIMVS. Minol et al 10 assessed the risk‐predictive value of the age‐adjusted Charlson comorbidity index (aa‐CCI) in MIMVS. They reported that patients with an aa‐CCI score ≥ 8 carry a substantially increased risk of mortality and adverse events 10 .…”
mentioning
confidence: 99%
“…Minol et al 10 assessed the risk‐predictive value of the age‐adjusted Charlson comorbidity index (aa‐CCI) in MIMVS. They reported that patients with an aa‐CCI score ≥ 8 carry a substantially increased risk of mortality and adverse events 10 . Therefore, the aa‐CCI score should be considered when assessing elderly patients with multimorbidities for MIMVS, in addition to the EuroSCORE II that is traditionally used 10 …”
mentioning
confidence: 99%
See 2 more Smart Citations